Pewna Seria Doświadczeń nad Efektem Skali przy Rozrywaniu Drutów Stalowych - Nowiński, J. (Engineering Transactions, 1956)
The scale effect or, in other words, the influence of absolute dimensions of structural elements on their strength has, together with the dispersion of the strength, a common background attributed to the non-homogeneity of materials. This probabilistic phenomenon was explained for brittle materials by W. Weibull, J. I. Frenkel and T. A. Kontorova. This note based on the author’s experiments on a wire of medium ductility is a contribution to this problem. Samples of wire (subjected to no previous treatment) 5 cm. and 50 cm. long were. tensile tested. From the curves of strength distribution assumed to be Gaussian curves it follows (Fig. 2) that the strength of short samples (A) is greater than that of long ones (B), which seems to confirm the scale effect and its connection with the non-homogeneity of the material.